Low-temperature preparation method of metal telluride nanorod

By reacting the tellurium source with hydrazine hydrate to form nano-scale tellurium rods under low temperature conditions and reacting with metal salt compounds, nano-scale rod-like metal tellurides with uniform morphology were prepared, which solved the problems of uncontrolled size and uneven morphology of the preparation of nano-scale metal tellurides in the prior art, and achieved an efficient, safe and environmentally friendly preparation method.

CN119911882APending Publication Date: 2025-05-02GUANGXI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411234792.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art has problems such as uncontrollable size, uneven morphology, complex one step, high temperature and high pressure, and the use of special additives and catalysts when preparing nano-scale metal telluride, making it difficult to achieve an efficient, safe and environmentally friendly preparation method.

Method used

At low temperature (70°C) or even room temperature, nanoscale tellurium rods are prepared by dissolving the tellurium source, surfactant and sodium hydroxide in water, adding hydrazine hydrate to react to form nanoscale tellurium rods, and then reacting with metal salt compounds. After centrifugation and drying steps, nanoscale rod-shaped metal tellurides with uniform morphology are prepared.

Benefits of technology

The synthesis of large-scale high-crystalline tellurium nanomaterials under low temperature conditions is achieved. The steps are simple, no special additives and catalysts are required, and it has good dimensional controllability and morphological uniformity, safe operation and environmentally friendly, reducing energy consumption and energy costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911882A_ABST
    Figure CN119911882A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature preparation method of a metal telluride nanorod, which comprises the following steps: sequentially dissolving a tellurium source, a surfactant and sodium hydroxide in ultrapure water to obtain a solution A, and then quickly adding hydrazine hydrate at 20-70 DEG C for reaction to obtain a solution B containing a nanoscale tellurium rod; dissolving a metal salt compound in ultrapure water to obtain a solution C; and adding an ascorbic acid solution into the solution C, uniformly mixing to obtain a solution D, adding the solution D into the solution B, reacting at room temperature, centrifuging to obtain a precipitate, washing the precipitate with distilled water, and drying to obtain the nanoscale rod-like metal telluride. According to the present invention, the large-scale synthesis of the high crystallinity tellurium nanometer material can be performed at the low temperature, the synthesis steps are simple, the use of any special additive and catalyst is not required, and the preparation method has advantages of good size controllability, good morphology uniformity, high operation safety, simple steps and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal telluride nanorods, and in particular relates to a low-temperature preparation method of metal telluride nanorods. Background Art

[0002] Metal tellurides are a class of semiconductor materials with outstanding and unique physical and chemical properties. Nanoscale metal tellurides have high photothermal conversion efficiency, excellent thermoelectric performance, optical properties, catalytic activity, semiconductor properties, surface plasmon effects and quantum confinement effects, and are widely used in biomedicine, photovoltaic devices, optoelectronic devices, sensors, heating / cooling devices, solar cells, catalysts and colorants, etc.

[0003] Nano-scale metal tellurides can be obtained through two approaches. The first is to directly synthesize the required tellurides, but this method has problems such as large size, complex synthesis steps, and high temperature and high pressure design; the second idea is to first synthesize tellurium elements of suitable size and uniform morphology, and then perform secondary synthesis to obtain tellurides. The synthesis of ideal tellurium elements also has challenges such as large size, complex synthesis steps, and high temperature and high pressure. At present, the preparation methods of nano-scale metal tellurides can be roughly divided into five types: solution method, gas phase method, mechanochemical method, hydrothermal method and electrochemical method. Among them, the mechanochemical method does not involve high-temperature operation, but its product quality is not high, and there are problems such as low purity, poor uniformity, and material contamination. The electrochemical method can be operated at room temperature, but its preparation conditions are strict and the operation requirements are extremely high. It requires precise control of current and voltage, and prevents problems such as electrode corrosion and side reactions. The other three methods all require reactions at relatively high temperatures (130 ~ 250 °C). Therefore, the exploration of preparation methods for nano-metal tellurides with controllable size, uniform morphology, simple operation, simple process, and green economy has attracted much attention. Summary of the invention

[0004] In view of the above-mentioned shortcomings, the present invention discloses a low-temperature preparation method of metal telluride nanorods, which can synthesize large-scale high-crystallinity telluride nanomaterials at low temperature (70°C) or even at room temperature. At the same time, the synthesis steps are simple and no special additives and catalysts are required. The preparation method has good size controllability and morphology uniformity, and has high operational safety, simple steps, and is environmentally friendly.

[0005] The present invention is achieved by adopting the following technical solutions: A low-temperature preparation method for metal telluride nanorods comprises the following steps: (1) A tellurium source, a surfactant, and sodium hydroxide are dissolved in ultrapure water in sequence to obtain a solution A, and then hydrazine hydrate is quickly added at 20 to 70° C. to react to obtain a solution B containing nano-scale tellurium rods; the solution A contains the following components in molar concentrations: 6 to 100 mM of a tellurium source, 1 to 50 mM of a surfactant, and 5 to 100 mM of sodium hydroxide; the volume ratio of the added hydrazine hydrate to the volume of the solution A is (0.1 to 1):1; the tellurium source is any one of sodium tellurite, tellurium oxide, and tellurium dioxide; (2) dissolving a metal salt compound in ultrapure water to obtain solution C, wherein the metal salt compound is a metal nitrate or a metal chloride; adding an ascorbic acid solution to solution C and mixing uniformly to obtain solution D; adding solution D to solution B obtained in step (1) and reacting at room temperature for 5 to 60 minutes; then centrifuging at 13,000 to 30,000 rpm for 15 minutes to obtain a precipitate; washing the precipitate with distilled water for 2 to 3 times and drying it at 60° C. for 12 to 24 hours to obtain a nano-rod-shaped metal telluride; the molar ratio of the metal salt compound in solution C to the tellurium source in solution A is (0.5 to 1):1.

[0006] The method of the present invention involves the following reactions: Formula (1): Na 2 TeO 3 +2N 2 H 4 ·H 2 O + 2NaOH → N 2 ↑+Te+5H 2 O+2Na 2 O Formula (2): 3Te+6NaOH→2Na 2 Te+Na 2 TeO 3 +H 2 O Formula (3): Cu(NO 3 ) 2 +Na 2 Te→CuTe+2NaNO 3 Formula (4): Cu(NO 3 ) 2 +Na 2 TeO 3 →CuTeO 3 +2NaNO 3 Formula (5): 2Cu(NO 3 ) 2 +2Na 2 Te→Cu 2 Te+Te+4NaNO3 Formula (6): (2−x)CuTe→Cu 2−x Te+(1−x)Te Wherein, formula (1) is the main reaction for preparing nano-scale tellurium rods, formula (2) is the transition step, and then the nano-scale rod-shaped telluride is prepared through the reactions shown in formulas (3) to (6).

[0007] Furthermore, in step (1), the surfactant is any one of a nonionic surfactant and a cationic surfactant.

[0008] Furthermore, in step (1), the surfactant is any one of polyvinyl pyrrolidone, polyethylene glycol and cetyl trimethyl ammonium bromide, and the average molecular weight of the polyvinyl pyrrolidone is 3000 to 900000.

[0009] Furthermore, in step (1), the reaction time of adding hydrazine hydrate is 0.2 to 336 hours.

[0010] Furthermore, in step (2), the metal is any one of iron, copper, manganese, chromium, nickel, zinc, cobalt, molybdenum, silver, cadmium, ruthenium, osmium, and bismuth.

[0011] Furthermore, in step (2), the concentration of the ascorbic acid solution is 0.5-3M.

[0012] Furthermore, in step (2), the volume ratio of the added ascorbic acid solution to the volume of solution C is (0.01-0.1):1.

[0013] Compared with the prior art, this technical solution has the following beneficial effects: 1. The present invention can synthesize large-scale high-crystallinity tellurium nanomaterials at a lower temperature (70°C) or even at room temperature. The synthesis steps are simple and do not involve high temperature and high pressure. No special additives or catalysts are required. The tellurium nanomaterial prepared by the present invention is a one-dimensional linear structure with uniform morphology, a width of 5 to 10 nm, a length of 50 to 500 nm, and a controllable length of the tellurium nanowire. It can be gradually observed that the tellurium element gradually changes from a tellurium point to an extremely fine tellurium nanowire. Then, the obtained tellurium nanowire is used to synthesize nanoscale metal tellurides, and nanoscale rod-shaped metal tellurides of corresponding sizes and uniform morphology can be obtained. Therefore, the present invention is a method for preparing nano-metal tellurides with size controllability, operational safety, simple steps, uniform morphology, environmental friendliness, and green environmental protection.

[0014] 2. Because the present invention can be completed at low temperature, it is safer and more operable than other technologies that require high temperature environments. At the same time, it can effectively reduce energy consumption and greatly reduce energy costs when it is applied industrially. The present invention can also enhance the intermolecular thermal motion and increase the reaction rate by appropriately increasing the temperature to 70°C, and obtain the target product with uniform morphology more quickly.

[0015] 3. The present invention is simple and easy to implement. The preparation process contains only H, O, and N elements in addition to the metal telluride elements themselves, which is green and environmentally friendly. The prepared nano-scale metal telluride material has semiconductor properties and has the advantages of uniform morphology and stability. It can be used in solar cells, high-precision materials, medical immunoassays and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a TEM image of the nanoscale tellurium rod described in Example 1.

[0017] Figure 2 This is a SEM image of the nano-rod-shaped metal copper telluride described in Example 1.

[0018] Figure 3 It is the ultraviolet absorption spectrum of the nano-telluride rods generated by the reaction at 50°C in the experimental example, wherein curves 1 to 10 represent the test results after the reaction for 15 min, 30 min, 45 min, 60 min, 90 min, 120 min, 180 min, 240 min, 300 min, and 600 min, respectively.

[0019] Figure 4 It is the ultraviolet absorption spectrum of the nano-telluride rods generated by the reaction at 60°C in the experimental example, wherein curves 1 to 10 represent the test results after the reaction for 10 min, 15 min, 30 min, 45 min, 60 min, 90 min, 120 min, 180 min, 240 min, and 300 min, respectively.

[0020] Figure 5 It is the ultraviolet absorption spectrum of the nano-telluride rods generated by the reaction at 70°C in the experimental example, wherein curves 1 to 10 represent the test results after the reaction for 10 min, 15 min, 30 min, 45 min, 60 min, 90 min, 120 min, 180 min, 240 min, and 300 min, respectively. DETAILED DESCRIPTION

[0021] The present invention is further described by the following examples, but is not intended to be limiting of the present invention. Specific experimental conditions and methods not specified in the following examples are conventional methods commonly known to those skilled in the art.

[0022] Embodiment 1: A low-temperature preparation method of metal telluride nanorods, comprising the following steps: (1) A tellurium source, a surfactant, and sodium hydroxide were dissolved in ultrapure water in sequence to obtain solution A. Then, hydrazine hydrate was quickly added at 70°C and reacted for 20 h to obtain solution B containing nano-scale tellurium rods. The solution was analyzed using a transmission electron microscope. The obtained transmission electron microscope image is shown in FIG. Figure 1 ; The solution A contains the following components in molar concentrations: 50 mM tellurium source, 10 mM surfactant, 40 mM sodium hydroxide; the volume ratio of the added hydrazine hydrate to the volume of solution A is 0.5:1; the tellurium source is sodium tellurite; the surfactant is polyvinyl pyrrolidone, and the average molecular weight of the polyvinyl pyrrolidone is 90,000; (2) copper nitrate is dissolved in ultrapure water to obtain a solution C with a concentration of 2.5125 g / mL; ascorbic acid solution is added to solution C and mixed evenly to obtain solution D; solution D is added to solution B obtained in step (1) and reacted at room temperature for 10 min, and then centrifuged at 20,000 rpm for 15 min to obtain a precipitate; the precipitate is washed three times with distilled water and dried at 60° C. for 18 h to obtain nano-scale rod-shaped metal copper telluride with a width of 20 to 30 nm and a length of 100 to 200 nm, and the nano-scale rod-shaped metal copper telluride with a width of 20 to 30 nm and a length of 100 to 200 nm is obtained, and the nano-scale rod-shaped metal copper telluride with a width of 20 to 30 nm and a length of 100 to 200 nm is analyzed by transmission electron microscopy. The obtained transmission electron microscopy image is shown in FIG. Figure 2 ; The molar ratio of copper nitrate in solution C to the tellurium source in solution A is 0.75:1; the concentration of the ascorbic acid solution is 1.5M; the volume ratio of the added ascorbic acid solution to the volume of solution C is 0.05:1.

[0023] Embodiment 2: A low-temperature preparation method of metal telluride nanorods, comprising the following steps: (1) A tellurium source, a surfactant, and sodium hydroxide are dissolved in ultrapure water in sequence to obtain a solution A, and then hydrazine hydrate is quickly added at 60°C to react for 36 hours to obtain a solution B containing nano-tellurium rods; the solution A contains the following components in molar concentrations: 30 mM of a tellurium source, 10 mM of a surfactant, and 10 mM of sodium hydroxide; the volume ratio of the added hydrazine hydrate to the volume of the solution A is 0.2:1; the tellurium source is sodium tellurite; the surfactant is polyvinyl pyrrolidone, and the average molecular weight of the polyvinyl pyrrolidone is 60,000; (2) copper nitrate is dissolved in ultrapure water to obtain a solution C with a concentration of 2.5125 g / mL; ascorbic acid solution is added to solution C and mixed to obtain solution D; solution D is added to solution B obtained in step (1) and reacted at room temperature for 20 min, then centrifuged at 15000 rpm for 15 min to obtain a precipitate; the precipitate is washed twice with distilled water and dried at 60° C. for 16 h to obtain nano-rod-shaped metal copper telluride; the obtained nano-rod-shaped metal copper telluride has a size of 25 to 35 nm in width and 80 to 180 nm in length; the molar ratio of copper nitrate in solution C to the tellurium source in solution A is 0.6:1; the concentration of the ascorbic acid solution is 1 M; the volume ratio of the added ascorbic acid solution to the volume of solution C is 0.03:1.

[0024] Embodiment 3: A low-temperature preparation method of metal telluride nanorods, comprising the following steps: (1) A tellurium source, a surfactant, and sodium hydroxide are dissolved in ultrapure water in sequence to obtain a solution A, and then hydrazine hydrate is quickly added at 50°C to react for 48 hours to obtain a solution B containing nano-scale tellurium rods; the solution A contains the following components in molar concentrations: 80 mM of a tellurium source, 20 mM of a surfactant, and 60 mM of sodium hydroxide; the volume ratio of the added hydrazine hydrate to the volume of the solution A is 0.5:1; the tellurium source is sodium tellurite; the surfactant is polyvinyl pyrrolidone, and the average molecular weight of the polyvinyl pyrrolidone is 100,000; (2) copper nitrate is dissolved in ultrapure water to obtain a solution C with a concentration of 2.5125 g / mL; ascorbic acid solution is added to solution C and mixed to obtain solution D; solution D is added to solution B obtained in step (1) and reacted at room temperature for 30 minutes; then centrifuged at 20,000 rpm for 15 minutes to obtain a precipitate; the precipitate is washed three times with distilled water and dried at 60° C. for 20 hours to obtain nano-rod-shaped metal copper telluride; the obtained nano-rod-shaped metal copper telluride has a size of 20 to 30 nm in width and 70 to 170 nm in length; the molar ratio of copper nitrate in solution C to the tellurium source in solution A is 0.85:1; the concentration of the ascorbic acid solution is 2 M; the volume ratio of the added ascorbic acid solution to the volume of solution C is 0.07:1.

[0025] Embodiment 4: A low-temperature preparation method of metal telluride nanorods, comprising the following steps: (1) A tellurium source, a surfactant, and sodium hydroxide are dissolved in ultrapure water in sequence to obtain a solution A, and then hydrazine hydrate is quickly added at 20°C to react for 336 hours to obtain a solution B containing nano-scale tellurium rods; the solution A contains the following components in molar concentrations: 100 mM of a tellurium source, 50 mM of a surfactant, and 100 mM of sodium hydroxide; the volume ratio of the added hydrazine hydrate to the volume of the solution A is 1:1; the tellurium source is sodium tellurite; the surfactant is polyvinyl pyrrolidone, and the average molecular weight of the polyvinyl pyrrolidone is 3000; (2) copper nitrate is dissolved in ultrapure water to obtain a solution C with a concentration of 2.5125 g / mL; ascorbic acid solution is added to solution C and mixed to obtain solution D; solution D is added to solution B obtained in step (1) and reacted at room temperature for 60 min, then centrifuged at 30,000 rpm for 15 min to obtain a precipitate; the precipitate is washed three times with distilled water and dried at 60° C. for 24 h to obtain nano-rod-shaped metal copper telluride; the obtained nano-rod-shaped metal copper telluride has a size of 20 to 35 nm in width and 300 to 400 nm in length; the molar ratio of copper nitrate in solution C to the tellurium source in solution A is 1:1; the concentration of the ascorbic acid solution is 3 M; the volume ratio of the added ascorbic acid solution to the volume of solution C is 0.08:1.

[0026] Embodiment 5: A low-temperature preparation method of metal telluride nanorods, comprising the following steps: (1) A tellurium source, a surfactant, and sodium hydroxide are dissolved in ultrapure water in sequence to obtain a solution A, and then hydrazine hydrate is quickly added at 70°C to react for 20 hours to obtain a solution B containing nano-scale tellurium rods; the solution A contains the following components in molar concentrations: 6 mM of a tellurium source, 1 mM of a surfactant, and 5 mM of sodium hydroxide; the volume ratio of the added hydrazine hydrate to the volume of the solution A is 0.1:1; the tellurium source is sodium tellurite; and the surfactant is polyethylene glycol; (2) copper nitrate is dissolved in ultrapure water to obtain a solution C with a concentration of 2.5125 g / mL; ascorbic acid solution is added to solution C and mixed to obtain solution D; solution D is added to solution B obtained in step (1) and reacted at room temperature for 5 min, then centrifuged at 13000 rpm for 15 min to obtain a precipitate; the precipitate is washed twice with distilled water and dried at 60° C. for 12 h to obtain nano-rod-shaped metal copper telluride; the obtained nano-rod-shaped metal copper telluride has a size of 15 to 30 nm in width and 100 to 200 nm in length; the molar ratio of copper nitrate in solution C to the tellurium source in solution A is 0.5:1; the concentration of the ascorbic acid solution is 0.5 M; the volume ratio of the added ascorbic acid solution to the volume of solution C is 0.1:1.

[0027] Embodiment 6: A low-temperature preparation method of metal telluride nanorods, comprising the following steps: (1) A tellurium source, a surfactant, and sodium hydroxide are dissolved in ultrapure water in sequence to obtain a solution A, and then hydrazine hydrate is quickly added at 35° C. to react for 72 hours to obtain a solution B containing nano-scale tellurium rods; the solution A contains the following components in molar concentrations: 40 mM of a tellurium source, 20 mM of a surfactant, and 20 mM of sodium hydroxide; the volume ratio of the added hydrazine hydrate to the volume of the solution A is 0.4:1; the tellurium source is tellurium oxide; and the surfactant is polyethylene glycol; (2) dissolving hexaammineruthenium chloride in ultrapure water to obtain solution C; adding ascorbic acid solution to solution C and mixing evenly to obtain solution D; adding solution D to solution B obtained in step (1) and reacting at room temperature for 20 minutes; then centrifuging at 20,000 rpm for 15 minutes to obtain a precipitate; washing the precipitate three times with distilled water and drying it at 60° C. for 22 hours to obtain nano-rod-shaped metal ruthenium telluride; the obtained nano-rod-shaped metal zinc telluride has a size of 20 to 30 nm in width and 115 to 250 nm in length; the molar ratio of hexaammineruthenium chloride in solution C to the tellurium source in solution A is 0.6:1; the concentration of the ascorbic acid solution is 1 M; the volume ratio of the added ascorbic acid solution to the volume of solution C is 0.04:1.

[0028] Embodiment 7: A low-temperature preparation method of metal telluride nanorods, comprising the following steps: (1) A tellurium source, a surfactant, and sodium hydroxide are dissolved in ultrapure water in sequence to obtain a solution A, and then hydrazine hydrate is quickly added at 50° C. to react for 48 hours to obtain a solution B containing nano-scale tellurium rods; the solution A contains the following components in molar concentrations: 80 mM of a tellurium source, 30 mM of a surfactant, and 80 mM of sodium hydroxide; the volume ratio of the added hydrazine hydrate to the volume of the solution A is 0.8:1; the tellurium source is tellurium dioxide; and the surfactant is hexadecyltrimethylammonium bromide; (2) dissolving silver nitrate in ultrapure water to obtain solution C; adding ascorbic acid solution to solution C and mixing uniformly to obtain solution D; adding solution D to solution B obtained in step (1) and reacting at room temperature for 30 minutes; then centrifuging at 20,000 rpm for 15 minutes to obtain a precipitate; washing the precipitate twice with distilled water and drying it at 60° C. for 20 hours to obtain nano-rod-shaped metallic silver telluride; the obtained nano-rod-shaped metallic silver telluride has a size of 20 to 35 nm in width and 100 to 250 nm in length; the molar ratio of silver nitrate in solution C to the tellurium source in solution A is 0.75:1; the concentration of the ascorbic acid solution is 2 M; the volume ratio of the added ascorbic acid solution to the volume of solution C is 0.02:1.

[0029] Experimental Example: Nano-scale rod-shaped copper telluride was prepared according to the method described in Example 1, wherein in step (1), after adding hydrazine hydrate, the reaction was carried out in a water bath at 50°C, 60°C, and 70°C, and then UV photography was performed at certain time intervals to obtain a continuously changing UV absorption spectrum. For specific results, see Figures 3 to 5 ,from Figures 3 to 5 It can be seen that within the low temperature range described in the method of the present invention, nano-tellurium rods can be stably generated, and as the reaction temperature increases, the reaction rate accelerates and the yield increases. However, when the reaction temperature is 70°C, the reaction rate and yield decrease after the reaction time exceeds 240 minutes.

[0030] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A low-temperature preparation method for metal telluride nanorods, characterized in that: The following steps are involved: (1) A tellurium source, a surfactant, and sodium hydroxide are dissolved in ultrapure water in sequence to obtain a solution A, and then hydrazine hydrate is quickly added at 20 to 70° C. to react to obtain a solution B containing nano-scale tellurium rods; the solution A contains the following components in molar concentrations: 6 to 100 mM of a tellurium source, 1 to 50 mM of a surfactant, and 5 to 100 mM of sodium hydroxide; the volume ratio of the added hydrazine hydrate to the volume of the solution A is (0.1 to 1):1; the tellurium source is any one of sodium tellurite, tellurium oxide, and tellurium dioxide; (2) dissolving a metal salt compound in ultrapure water to obtain solution C, wherein the metal salt compound is a metal nitrate or a metal chloride; adding an ascorbic acid solution to solution C and mixing uniformly to obtain solution D; adding solution D to solution B obtained in step (1) and reacting at room temperature for 5 to 60 minutes; then centrifuging at 13,000 to 30,000 rpm for 15 minutes to obtain a precipitate; washing the precipitate with distilled water for 2 to 3 times and drying it at 60° C. for 12 to 24 hours to obtain a nano-rod-shaped metal telluride; the molar ratio of the metal salt compound in solution C to the tellurium source in solution A is (0.5 to 1):

1.

2. The low-temperature preparation method of metal telluride nanorods according to claim 1, characterized in that: In step (1), the surfactant is any one of a nonionic surfactant and a cationic surfactant.

3. The low-temperature preparation method of metal telluride nanorods according to claim 1, characterized in that: In step (1), the surfactant is any one of polyvinyl pyrrolidone, polyethylene glycol and cetyl trimethyl ammonium bromide, and the average molecular weight of the polyvinyl pyrrolidone is 3000 to 900000.

4. The low-temperature preparation method of metal telluride nanorods according to claim 1, characterized in that: In step (1), the reaction time of adding hydrazine hydrate is 0.2 to 336 hours.

5. The low-temperature preparation method of metal telluride nanorods according to claim 1, characterized in that: In step (2), the metal is any one of iron, copper, manganese, chromium, nickel, zinc, cobalt, molybdenum, silver, cadmium, ruthenium, osmium and bismuth.

6. The low-temperature preparation method of metal telluride nanorods according to claim 1, characterized in that: In step (2), the concentration of the ascorbic acid solution is 0.5 to 3 M.

7. The low-temperature preparation method of metal telluride nanorods according to claim 1, characterized in that: In step (2), the volume ratio of the added ascorbic acid solution to the volume of solution C is (0.01-0.1):1.

Citation Information

Patent Citations

  • Preparation method of nanoscale rodlike bismuth telluride nanomaterial

    CN104555952A

  • Preparation methods of tin telluride nanorods and tin telluride based binary metal telluride nanorods

    CN107539961A

  • Preparation method of indium telluride nanometer lines

    CN108190847A

  • Metal telluride nanotube and universal preparation method thereof

    CN113582143A

  • Method for manufacturing bismuth telluride nanotubes and bismuth telluride nanotubes having high aspect ratio manufactured by same

    KR1020140025709A